Active controllable and flexible winding needle an option to reduce the complexity of needle winding machines and the stress on enameled wire - Schneider, Michael; Bickel, Benjamin; Risch, Florian; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014 - Proceedings, 2014)
State of the art needle winding technologies have one thing in common-a stiff, straight or bent winding needle. During the manufacturing process of electrical machines, the used enameled wires are exposed to deformations which decrease the insulation resistance against partial discharge and disruptive discharge. A reduced insulation resistance shortens the product lifecycle. The active controllable and flexible winding needle is able to adapt its form to the mechanical behavior of wire during any deformation and thus to wind wires more gently. In the production of electrical machines the copper filling factor in the slot is often considered key. To provide the needed space for the tools to move through the stator while distributing the windings, the winding tools have to be rather small or the inner diameter of the stator has a minimum whereat the feasibility for needle winding is still present. With the actively controllable and flexible winding needle no more extra axis and other constructions are necessary to fulfill the requirements of a small tool at maximum flexibility.
CRIS-Team Scopus Importer:2023-03-07
Keywords: distributed winding; winding guide nozzle; winding needle; winding technology

Analysis of the Rotary Cutting Process of Electrical Steel on Basis of a Toroidal Core Test - Hubert, Markus; Ziegler, Marco; Kutter, Simon; Schneider, Michael; Weigelt, Michael; Franke, Jörg; Hackert, Juergen; Mehlhorn, Marcus (2016 6th International Electric Drives Production Conference (E/DPC), 2016)
Rotary cutting of electrical steel strip is an innovative, but largely unexplored process. By state of the art a derivation of achievable process and product quality is not sufficiently possible yet. Within this publication, a series of experiments to rotary cut toroidal core specimens will be presented. With toroidal core tests on one the hand, the rotary cutting process itself is analyzed and on the other hand the results of the sample analysis reveal the process influences. Finally, a classification of the rotary cutting process into existing processing technologies of electrical steel strip is feasible with respect to its limits and possibilities.

Comparison of Additive Balancing Processes for Rotors in the Context of High Speed Electric Traction Motors - Masuch, Michael; von Lindenfels, Johannes; Seefried, Johannes; Mayr, Andreas; Schneider, Michael; Weigelt, Michael; Kühl, Alexander; Franke, Jörg; Hemmer, Christian (2019 9th International Electric Drives Production Conference (EDPC), 2019)
In the ongoing development of electric traction motors with increasing volumetric power density, concepts are being developed for rotational speeds of more than 30,000 rpm. These motors require an especially high balancing quality. Due to the unavoidable material and production fluctuations, a tuning of the mass distribution regarding the rotation axis is necessary. This balancing can be achieved by subtractive or additive process alternatives. In this paper, an overview of current balancing approaches is given first. Based on this, the potentials and challenges of additive balancing methods, which directly apply material to the lamination stack, are explained. In this context, two joining processes, namely ultrasonic welding and laser beam welding, are examined in more detail on the basis of practical experiments. In particular, influences on the quality of the lamination stack are considered.<br
Keywords: balancing; rotor; electric motor production; manufacturing; NVH; laser beam welding; ultrasonic welding

Fertigungsbegleitende Qualitätskontrolle in der Elektromotorenfertigung - Meyer, Alexander Wilhelm; Abersfelder, Sandra; Urban, Nikolaus; Schneider, Michael; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2017)
Keywords: E|DRIVE

Influence of cutting edge on core loss induced through various manufacturing parameters - Schneider, Michael; Hubert, Markus; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Various manufacturing processes in the production-from laminated magnetic steel sheets to an assembled stator-affect the electromagnetic characteristics. Often the manufacturing processes of the process step cutting are compared to highlight differences. Many publications have already dealt with this issue over several decades. Flux distribution, loss and the B-H characteristics are not the same, whether an electrical sheet with defined geometry is cut with a laser, water jet, electrical discharge machining, rotational cutting or with a punching machine. It is adequately researched that differences in loss behavior occur. Within the various technologies, a comparison of varied production parameters is scarcer. Here, interesting studies result when considering the specific hysteresis and eddy current losses in the variation of the process parameters on the relative position of the rolling direction, average speed, distance energy and the comparison between fiber and CO2-Laser with different focus diameters. This paper deals with the comparison of cut sheets made from electrical steel with grade M270 35A. The metal strips investigated were prepared on dimensions of 150×150 mm and 37,5×150 mm using the above parameter variation and analyzed in a single sheet tester from Brockhaus regarding their loss behavior.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cutting; iron losses; measurement; sheet metal

Intelligent fault diagnosis in Industry 4.0 - New opportunities for the sophisticated diagnosis in automated production environments - Fleischmann, Hans; Kohl, Johannes; Schneider, Michael; Franke, Jörg (wt Werkstattstechnik - Online, 2015)
The increasing complexity of sophisticated production plants poses new challenges in the field of technical maintenance. The initial step in the repair procedure is a problem root-cause analysis. As a key enabler of the Industry 4.0 cyber-physical systems form the core of novel assistant systems, which deliver more efficient diagnostic mechanisms for production facilities.
CRIS-Team Scopus Importer:2023-03-07

Kräfte-und Belastungsermittlung: Bei der Handhabung von Statorblechpaketen in der Fertigung von Elektromotoren - Schneider, Michael; Zahner, Michael; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2015)
Due to the proven low shear stress and its favorable allocation in the contact area between the individual sheets, the adhesive bonding process or baked enamel process represent packaging technologies with good electromechanical properties. For each individual application, it remains to weigh whether the lower eddy current losses justify the higher energy and time which is needed by using adhesive bonding or baked enamel. From a purely mechanical point of view, there are no concerns about the rigidity of the lamination stack during the handling process.
CRIS-Team Scopus Importer:2023-03-07

Neuartiger Ansatz zur flexiblen Fertigung verlustoptimierter Statorblechpakete - Schneider, Michael; Urban, Nikolaus; Meyer, Alexander Wilhelm; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2017)
Keywords: E|DRIVE

Optimization approach of wireless power transfer systems for electric vehicles from a process and material perspective - Risch, Florian; Kraner, Sebastian; Schneider, Michael; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014 - Proceedings, 2014)
Modern Wireless Power Transfer (WPT) systems for electric vehicles (EVs) have already shown their potential for high-power transfer efficiency in many prototypes and trials. However, WPT for EVs is a particularly demanding application and still in its early commercialization phase. There are still some barriers to overcome for a successful and large-scale implementation of WPT systems to become a preferred method for recharging EVs. For practical application in an EV, power pads need to meet strict automotive requirements (ISO/TS 16949:2009 certification). A thorough material and process analysis must be used to identify and assess failure modes and effects preventatively. In this context, it is the objective of this paper to present an automated test bench approach to precisely evaluate WPT systems with a focus on the process and material perspective.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric vehicles; process and material parameters; test bench concept; wireless power transfer systems

Potentials of the Rotary Cutting Process for Electrical Steel Strip - Ziegler, Marco; Schneider, Michael; Hubert, Markus; Franke, Jörg (2018 8th International Electric Drives Production Conference, EDPC 2018 - Proceedings, 2018)
To minimize eddy current losses, stators and rotors are traditionally designed laminated. For this purpose, the single sheets are electrically separated from each other by an insulation layer. The production of electrical steel laminations for rotor and stator stacks is divided into the steps of cutting, stacking and joining. Currently, there are several possibilities for each process step. The selection of the suitable process depends on the application, quantity and size of the electrical steel laminations. In mass production, the electrical steel strip is separated mainly by stamping. In prototype manufacturing and for small series, the lamination is cut out by laser. In addition, wire EDM and water-jet cutting are applied in specific applications. Rotary cutting of electrical steel strip is a process that is not yet used in industry. However, the novel approach has a great potential, since investment and tooling costs are relatively low. Furthermore, the process is suitable for the production of thin laminations (smaller than 0.3 mm) which are used in traction motors for electric vehicles.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Electrical Steel Processing; Laser Cutting; Rotary Cutting; Stamping

Relation of joining parameters of stator core production and iron loss - Schneider, Michael; Urban, Nikolaus; Franke, Jörg (2017 7th International Electric Drives Production Conference, EDPC 2017 - Proceedings, 2018)
The demand for environmentally friendly and sustainable mobility leads to the increasing spread of electric vehicles. An important part of the electric drive is the stator. This is made up of many laminated steel sheets. The production quality of such a laminated stator core is effected by the essential process steps of cutting, joining and winding. The causes of potential losses can arise in each of these phases. At high frequencies, the eddy current losses dominate the iron losses and thus also the major part of the total losses. Different manufacturing technologies for joining the laminations are often compared in literature to highlight differences. Within the scope of this publication, different joining technologies are compared with respect to the hysteresis and eddy current losses influenced by them. For this purpose, differently manufactured ring core samples with multiple production parameters are examined. In particular the increase of the iron losses caused by the local and global generation of conductive paths in the sheet metal package is the focus of interest here. Subsequently, the losses resulting from baked resin and welding joining technology are determined and compared by means of measurements. We present industry relevant results by considering the specific hysteresis and eddy current losses according to DIN DIN EN 60404-6. The experiments are carried out varying different process parameters like welding seams, welding energy, feed speed and pressure, baking time and temperature with regard to diameters of ring core samples.
CRIS-Team Scopus Importer:2023-03-07
Keywords: baked varnish; iron losses; laminated core; measurement; sheet metal; welding

Resonant method for the measurement of quality of laminated cores - Schneider, Michael; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
Measurement of the electromagnetic properties of soft magnetic materials becomes increasingly important with the demand for more efficiency in electric machines. In addition to the B-H characteristic and the permeability, which is necessary in a FEM program for the calculation of electromagnetic fields for realistic simulation of an electrical machine, today's measurement methods obtain additional information on the quality of finished metal package. Thus, it is possible to identify the engine iron losses, divided into hysteresis and eddy current losses. But under the current state of the art, only samples are provided for checking the quality of laminated cores according to the process steps sheet metal cutting, stacking and packing. For this, several stators are taken from current production and loss measurement is performed. For the measurement of the core loss (toroidal or stator geometry) are each wound a primary and a secondary winding on a sample. The wrapping is done by hand and is therefore very time-consuming. An inline measurement of all stators from a production line is not possible with this effort. To increase the quality and safety of the transparency of the manufactured products a 100% inspection is interesting. In terms of process control of the whole production line a 100% measurement strategy provides the framework for a comprehensive analysis for refining the appropriate feedback variables (tool change times, machine parameters, etc.). The losses should be recorded with the new measurement method during manufacturing and provided to the parent manufacturing control system as information. Thus machine parameters can be adjusted directly or tools are detected at the limit of wear and can be rapidly replaced to ensure a consistently high quality of sheet metal packages. A new method of quality assurance for laminated cores will be presented in this paper.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cutting; iron losses; measurement method; sheet metal; stacking

StroMiS - Studie zur technisch-wirtschaftlichen Analyse der Stromerzeugung aus Mikrokraftwerken in Serienfertigung - Scholz, Michael; Kühl, Alexander; Höft, Annika; Landgraf, Maximilian; Schneider, Michael; Böhm, Ralf; Badel, Gregor; Lothes, Gerald; Angerer, Kerstin; Hohmann, Andrea; Simon, Peter; Konwitschny, Fabian; et al. (2019)

The development and validation of a segmented rotor design for electric motors in hybrid vehicle applications - Franke, Jörg; Albrecht, Thomas; Lamprecht, Erik; Hubert, Markus; Schneider, Michael (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2014, 2014)
This paper presents investigations into the development and validation of a new segmented rotor design. A segmented rotor design avoids the significant waste of the precious electric steel material and therefore leads to cost reductions. For validation of the segmented rotor design, a finite element method simulation, tensile tests, centrifugal stress tests and iron loss measurements were carried out. The simulation results allow for determining of a segmented rotor design. The tensile and centrifugal test results further confirm the capability of the segmented rotor design for serial applications. The results confirm that the rotor design does not generate additional iron losses. © 2014 IEEE.
Keywords: electric mobility; iron losses; manufacturing processes; rotor segmentation